2020
DOI: 10.1210/endocr/bqaa098
|View full text |Cite
|
Sign up to set email alerts
|

Steroids Regulate SLC2A1 and SLC2A3 to Deliver Glucose Into Trophectoderm for Metabolism via Glycolysis

Abstract: Abstract The conceptuses (embryo/fetus and placental membranes) of pigs require energy to support elongation and implantation, and amounts of glucose and fructose increase in the uterine lumen during the peri-implantation period. Conceptuses from day 16 of pregnancy were incubated with either 14C-glucose or 14C-fructose and amounts of radiolabeled CO2 released from the conceptuses measured to determine rates of oxidation of glucose and fructose. Glucose and fruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 54 publications
5
14
0
Order By: Relevance
“…Particularly, our study presents the potential ligand-receptor-pathway cascades landscape at the maternal-fetal interface. Our reanalysis revealed an enhanced glycolysis in the ovine conceptus by implantation stage, which is line with results reported in mice, pigs and cattle (54)(55)(56)(57). More recently, the bovine conceptus metabolomic pro ling based on conditioned media analysis suggested that conceptus-derived glycolytic metabolite may diffuse to microenvironment at maternal-fetal interface by implantation stage (57).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Particularly, our study presents the potential ligand-receptor-pathway cascades landscape at the maternal-fetal interface. Our reanalysis revealed an enhanced glycolysis in the ovine conceptus by implantation stage, which is line with results reported in mice, pigs and cattle (54)(55)(56)(57). More recently, the bovine conceptus metabolomic pro ling based on conditioned media analysis suggested that conceptus-derived glycolytic metabolite may diffuse to microenvironment at maternal-fetal interface by implantation stage (57).…”
Section: Discussionsupporting
confidence: 89%
“…3D) using previously published transcriptomic data (49). The results showed a tendency towards enhanced glycolysis, which agreed with that reported in other species (54)(55)(56)(57). Given that glycolysis is less e cient in terms of ATP production compared with oxidative phosphorylation, it has been thought that there might be non-energy providing functions of glycolysis in peri-implantation embryos (58,59).…”
Section: Construction Of a Repository Of The Potential Ligand-receptor-pathway Cascadesupporting
confidence: 88%
“…3D) using previously published transcriptomic data [45]. The results showed a tendency towards enhanced glycolysis, which agreed with that reported in other species [48][49][50]. Given that glycolysis is less e cient in terms of ATP production compared with oxidative phosphorylation, it has been thought that there might be non-energy providing functions of glycolysis in peri-implantation embryos [51,52].…”
Section: Construction Of a Repository Of The Potential Ligand-receptorpathway Cascadesupporting
confidence: 88%
“…As shown in Figure 1D , we observed that SLC2A3 (GLUT-3), SLC35F6 , ABCC1 (MRP1), SLC22A18 (efflux transporter-like protein), and SLC17A5 (acidic Sugar Transporter) are significantly inhibited, while ABCC4 (MRP4) is significantly up-regulated. The down-regulation of SLC2A3 and SLC17A5 implied that PDT might affect the cellular uptake of glucose into brain parenchyma tissue, owing to that these genes are highly associated with glucose uptake ( 33 , 34 ). ABCC1 , ABCC4 , and SLC22A18 participate in the drug resistance pathway ( 35 ).…”
Section: Resultsmentioning
confidence: 99%